Increasing Legal Awareness of Weaving Micro, Small, and Medium Enterprises To The Obligation To Pay Taxes In Rote Ndao Regency Is Reviewed From Government Regulation Number 23 Of 2018 Concerning Income Tax - Terfena Leoh, Fesly; Mario Monteiro, Yosef; Ratu Udju, Hernimus (CV. Publikasi Indonesia, 2023)
The Micro, Small and Medium Enterprises Tax is part of the tax category that has very promising potential in the revenue of the Rote Ndao Region. However, with the increasing number of Micro, Small and Medium Enterprises Weaving Ikat, there are various phenomena that have emerged, including micro, small and medium enterprises owners not fulfilling their obligations to register and pay taxes. Based on the observations of the author, the background of the subject matter can be formulated: (1) To what extent is the Legal Awareness Raising of Micro, Small and Medium Enterprises Weaving Ikat Against the Obligation to Pay Taxes in Rote Ndao District? (2) What are the Factors Inhibiting the Improvement of Legal Awareness of Micro, Small and Medium Enterprises Weaving Ikat Against the Obligation to Pay Taxes in Rote Ndao District?. To answer these problems, research is carried out using the Qualitative Descriptive Analysis Method in accordance with the data obtained while still paying attention to legal theories, principles and rules, so this research is a research sourced from primary, secondary, and tertiary data using an empirical juridical approach. The results of this study show: (1). Increasing Tax Law Awareness of micro, small and medium enterprises owners in Rote Ndao Regency is still minimal because there is still an unconsciousness of their obligations as taxpayers. (2) Factors that hinder the increase in legal awareness of Micro, Small and Medium Enterprises Weaving Ikat, namely due to the absence of Regional Regulations on taxpayers, lack of income earned by Micro, Small and Medium Enterprises actors, lack of knowledge and minimal understanding from taxpayers